Genotype and phenotype variability in Sjögren‐Larsson syndrome. Issue 2 (26th November 2018) - Weustenfeld, Maximilian; Eidelpes, Reiner; Schmuth, Matthias; Rizzo, William B.; Zschocke, Johannes; Keller, Markus A.
Abstract: The Sjögren–Larsson syndrome (SLS) is a rare autosomal recessive disorder caused by pathogenic variants in the ALDH3A2 gene, which codes for fatty aldehyde dehydrogenase (FALDH). FALDH prevents the accumulation of toxic fatty aldehydes by converting them into fatty acids. Pathogenic ALDH3A2 variants cause symptoms such as ichthyosis, spasticity, intellectual disability, and a wide range of less common clinical features. Interpreting patient‐to‐patient variability is often complicated by inconsistent reporting and negatively impacts on establishing robust criteria to measure the success of SLS treatments. Thus, with this study, patient‐centered literature data was merged into a concise genotype‐based, open‐access database (www.LOVD.nl/ALDH3A2 ). One hundred and seventy eight individuals with 90 unique SLS‐causing variants were included with phenotypic data being available for more than 90%. While the three lead symptoms did occur in almost all cases, more heterogeneity was observed for other frequent clinical manifestations of SLS. However, a stringent genotype–phenotype correlation analysis was hampered by the considerable variability in reporting phenotypic features. Consequently, we compiled a set of recommendations of how to generate comprehensive SLS patient descriptions in the future. This will be of benefit on multiple levels, for example, in clinical diagnosis, basic research, and the development of novel treatment options for SLS. Abstract : In this manuscript we analyse the genotypic and phenotypic variability of 178 Sjögren‐Larsson Syndrome (SLS) cases and makes this information available in a concise genotype‐based, open‐access database (http://www.LOVD.nl/ALDH3A2 ). We describe the broad, heterogenic spectrum of phenotypes among SLS patients, which is caused by patient‐to‐patient variability in combination with inconsistent reporting in literature. Furthermore, based on these data we established a set of guidelines that will ensure comprehensive SLS patient reporting in the future.